Morphological remarks on Adelphydraena amazonica Perkins & Ribera, 2020 and new records of two other Hydraenidae from Brazil (Coleoptera) - Benetti, Cesar João; Valladares, Luis Felipe; Delgado, Juan Antonio; Hamada, Neusa (Zootaxa, 2021)
Undescribed morphological features of Adelphydraena amazonica Perkins & Ribera, 2020 are provided based on material collected in the type locality (Amazonas State, northern Brazil). Aedeagus, male sternite X, last female abdominal segments and spermatheca are illustrated and described for the first time. Habitat information on the type locality is also included. New records on two Brazilian Hydraenidae species are provided. Copyright © 2021 Magnolia Press
Keywords: Amazonia; Aquatic Coleoptera; Aquatic insects; Male description; Minute moss beetles